Integration of Gestalt Counseling in Pesantren Counseling Management System: A Strategy to Improve the Psychological Well-Being of Students’ - Fathor Rozi; Nur Afidah Udhiyah; Muhammad Munif; Hasan Jali (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This study aims to explore the integration of the Gestalt Counseling approach into the counseling management system of Islamic boarding schools to improve the psychological well-being of students. The research approach used is qualitative with a case study design. Data collection was conducted through participatory observation, in-depth interviews, and document analysis, which were then analyzed using the Miles and Huberman model. The results of the study indicate that the Gestalt approach is effective in increasing self-awareness, strengthening interpersonal relationships and empathy, and encouraging a more humanistic and responsive transformation of the counseling management system. Students become more capable of recognizing and expressing their emotions, building healthy social relationships, and demonstrating personal responsibility in solving problems. These findings prove that modern psychological approaches such as Gestalt can be harmoniously contextualized within an Islamic educational environment. Implicitly, Islamic boarding schools can develop an integrative counseling model that combines religious values with contemporary psychological approaches to create an educational ecosystem that supports the holistic spiritual, emotional, and social development of students. This research also opens up opportunities for the development of a more adaptive humanistic-based Islamic counseling theory tailored to the needs of students in the modern era, while accommodating the psychological dynamics faced by students in their daily lives.